Market Probability and Business Strategy Design in Indian Retail Sector-An Empirical Study - Upadhyaya , Makarand (Gyan Management Journal, 2012)
The present study aims at analysis of market probability for setting up a new supermarket in a specified area. The scope of the research includes undertaking a market research with the help of a survey and then analyzing the prospects. Research Methodology for the same is based on an exploratory survey for both customers and retailers. Analysis reveals that there is no significant relation between the number of years of residence and the place of purchasing grocery items. There is tremendous potential for the super marketers to lure the customers to buy products from their superstores. The research findings show that 51 percent people have attributed quality to be the most important criteria for selecting a store. This clearly indicates that the quality of products should be taken utmost care. Even if the distance is a bit more, people don't mind buying products from stores where good quality is assured. One of the main reasons given by the respondents for not visiting a supermarket again is that credit is not offered. The ideal site location and the average amount of customer traffic expected can be easily calculated with the help of Huff's gravity model. CPFR (Collaboration, Planning, Forecasting and Replenishment) is the model which should be followed. The positioning of the supermarket should be in such a way that the people are convinced that the products bought from the supermarkets would give a complete VFM (Value for Money). Excellent customer service has to be the major factor while opening up the supermarket.
Keywords: Quality; Huff's gravity model; CPFR; VFM; Customer loyalty programmes